Decision support system for the determination of subsided food recipients for family Poor with ahp method on Kelurahan Mangga - hendra marpaung; Petti Indrayati Sijabat (Jurnal ICT : Information and Communication Technologies, 2021)
In accordance with the regulations that have been determined by the Mangga Village Head Office to obtain Subsidized Food Materials, criteria are needed to determine who will be selected to receive subsidized food. . To assist the determination in determining someone who deserves to receive subsidized food, a decision support system is needed. One method that can be used for Decision Support Systems is to use AHP (Analytical Hierarchy Process). In this study, a case will be raised, namely looking for the best alternative based on predetermined criteria using the AHP (Analytical Hierarchy Process) method to calculate the method in this case. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is the one who is entitled to receive subsidized food based on the specified criteria. The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the poor. in this case the intended alternative is the one who is entitled to receive subsidized food based on the specified criteria. The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the poor. in this case the intended alternative is the one who is entitled to receive subsidized food based on the specified criteria. The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the poor.